PENGARUH DISCHARGE PLANNING TERHADAP PENAMBAHAN BERAT BADAN PADA BBLR DALAM 3 BULAN PERTAMA DI KOTA SEMARANG - Nur Dian Rakhmawati; Fitri Haryanti; Tunjung Wibowo (Jurnal Keperawatan Anak, 2013)
Background: Discharge planning is one of the methods needed to improve the knowledge of mother or parents in providing appropriate care, especially in the provision of nutrition for Low birth weight infants(LBW). Weight gain given an overview of baby health status. Lack of information on how to breastfeed and how to care LBW at home rightly, makes family less understanding about the importance of nutritionfor the growth and development of infants.Objective: Proving the effect of discharge planning for gaining of weight on LBW in first 3 months.Methods: The study was quasi-experimental non equivalent control design. Subjects were that meet the inclusion and exclusion criteria. Number of samples was 24 for the intervention and 24 for the control. Evaluation was done every 2, 4, 6, 8, 12 weeks to measure the weight gain on LBW in the first 3 months. Analysis was using Chi-Square (ujiX2), t-test and multivariable logistic regression.Results: On statistical test was obtained result that discharge planning affect on LBW weight gain in 3 months (RR = 2.2; CI = 1.35 to 3.59, p = 0.000), discharge planning also affects the full breastfeedingfor 3 months (RR = 4.2; CI = 1.68 to 10.78, p = 0.000), full breastfeeding was also influenced on the weight gain of infants (RR = 2.1; CI = 1.39 to 3.30, p = 0.000)Conclusion: At discharge planning was shown significantly affect to the gaining of weight in the first 3 months of LBW.